Risk of cervical intraepithelial neoplasia in women with glomerulonephritis. - Hartveit, F (1991)
OBJECTIVE--To investigate the occurrence of cervical intraepithelial neoplasia in women with glomerulonephritis and its possible association with immunosuppressive treatment. DESIGN--Retrospective study of cytological or histological specimens from women presenting with glomerulonephritis and a group of case and age matched controls. SETTING--University department of pathology, Norway. PATIENTS--81 women presenting with glomerulonephritis from 1981 to 1988, from whom gynaecological cytological or histological specimens were available. A group of 162 case and age matched controls. MAIN OUTCOME MEASURES--Age when glomerulonephritis of cervical intraepithelial neoplasia was diagnosed, type and characteristics of kidney lesion, stage of cervical intraepithelial neoplasia and presence of human papillomavirus, use of immunosuppressive treatment. RESULTS--Cervical intraepithelial neoplasia was more common in women with glomerulonephritis than in their controls (16/81 (20%) v 7/162 (4%), p less than 0.001) and was more advanced in those with glomerulonephritis than in the controls (9/81 (11%) of the study group had grade III cervical intraepithelial neoplasia compared with 1/162 (1%) of the controls). The increased occurrence of cervical lesions was independent of the use of immunosuppressive treatment, but the individual lesions tended to be more advanced when it was used (four of the seven cervical lesions in women with glomerulonephritis who had received immunosuppressive treatment were carcinoma in situ). Of the nine cervical lesions tested, seven were virus associated. CONCLUSION--Women with glomerulonephritis should have regular cervical smears, irrespective of their use of immunosuppressive treatment.